Evaluación farmacognóstica y cuantificación de fenoles totales de las hojas de Aloysia citrodora "cedrón”. - Valderrama Melquiades, Erminda Beatriz (2019)
The objective of this research was to determine the pharmacognostic study and quantify the content of total phenols of the leaves of Aloysia citrodora "cedrón" from the province of Otuzco La Libertad One copy of the plant species was duly identified in the Herbarium Truxillense (HUT) with code N°59746. The pharmacognostic study included the determination of macromorphological characteristics, its weight being: 0.07 g and dimensions: width (1 cm ± 0.1683), and length: (4.5 cm ± 0.7123 ), the physicochemical parameters of quality control: foreign matter (1%), residual humidity (9.99%), total ash (7.48% ± 0.7203), water soluble ashes (1.57% ± 0 , 1598) and ash insoluble in acid (1.29% ± 0.9539), water soluble substances: (11.98% ± 0.1959), ethanol of 50 ° GL: (15.56% ± 0.2718 ), 70 ° GL ethanol (14.69% ± 0.2659) and 96 ° GL ethanol: (7.81% ± 0.1969), which are within the range of missable by pharmacopoeias; the phytochemical screening proposed by Migdalia Miranda, where the presence of phytoconstituents such as alkaloids, flavonoids, steroids, anthocyanidins, reducing sugars was identified. Quantification of total phenols was carried out by the folin-ciocalteau method, where it was obtained for the ethanol extract : 2.4016 g / g